Peace time : cease-fire agreements and the durability of peace - Fortna, Virginia Page (Princeton University Press, 2004)
How to maintain peace in the aftermath of war is arguably one of the most important questions of the post-Cold War era, and one of the least explored issues in the study of war and peace. This book explains why some cease-fire fall apart quickly while others last for years.